2007
DOI: 10.1111/j.1744-7410.2007.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Tantulum elegans reloaded: a computer‐based 3D‐visualization of the anatomy of a Caribbean freshwater acochlidian gastropod

Abstract: Abstract. Acochlidian gastropods combine several aberrant biological and morphological features. The poorly known Caribbean Tantulum elegans is one of the few opisthobranch species inhabiting a freshwater system, and the only one found in muddy interstices of a Caribbean mountain spring swamp. Morphological details of this tiny species were either unknown or not fully reliable, especially with regard to the complex central nervous and reproductive systems. We critically re‐examined original paratype section s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(79 citation statements)
references
References 27 publications
3
76
0
Order By: Relevance
“…This type is present in all limnic acochlidian species, i.e. the small Caribbean limnic Tantulum elegans [66] and the large Indo-Pacific Acochlidiidae [44], in the brackish Pseudunela espiritusanta [43] and the at least temporary brackish P. cornuta [17]. Thus, the type of the excretory system in acochlidians is not strictly correlated with the habitat in acochlidian species: marine acochlidian species have either a type I or IIa excretory system with a simple or a complex kidney, respectivly.…”
Section: Discussionmentioning
confidence: 98%
“…This type is present in all limnic acochlidian species, i.e. the small Caribbean limnic Tantulum elegans [66] and the large Indo-Pacific Acochlidiidae [44], in the brackish Pseudunela espiritusanta [43] and the at least temporary brackish P. cornuta [17]. Thus, the type of the excretory system in acochlidians is not strictly correlated with the habitat in acochlidian species: marine acochlidian species have either a type I or IIa excretory system with a simple or a complex kidney, respectivly.…”
Section: Discussionmentioning
confidence: 98%
“…This is true of the microhedylacean Acochlidia, which are exclusively found in interstitial spaces in sediment, and show a tendency toward reduction of complexity in major organ systems [7]. In contrast, hedylopsacean Acochlidia, whose evolution involves several habitat shifts from marine interstitial to amphibious or freshwater benthic habitats, subsequently possess complex excretory and reproductive systems (e.g., [75-78]). Generally, there is little morphological variation in all major organ systems even at family- and genus-level see [7], but the morphological uniformity in global Pontohedyle is most striking.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may, however, not affect the presence of a double root. In more recent studies, double rooted ‘rhinophoral’ ganglia were found in rhodopemorphs (not Euthyneura according to preliminary molecular data, [44]) and, inside Euthyneura, so far only among panpulmonate pyramidelloids, ‘opisthobranch’ sacoglossans and acochlidians [47,53,81]. Several other panpulmonates possess the neurosecretory procerebrum with double roots (see [40,86]).…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether these double roots per se are homologous, since it is so far not clear which nerve tracts originally fused (or divided) to form the double roots; ontogenetic data on this particular phenomenon are entirely lacking. However, different nerves of the aforementioned ‘basic’ set were suggested to play part in the double root: some examples are the putative inclusion of nerves N3+4 in the sacoglossan Elysia Risso, 1818, Gascoignella Jensen, 1985 or Platyhedyle ([81]: p. 400], [22,53]) or the N3 + optic nerve in some acochlidians [14,25,47,52]. In Helminthope , one root of the N3 emerges close to the N2, therefore the double-rooted N3 may be product of partial fusion of fibers of N2+3, or one root may have originated from the otherwise missing N1.…”
Section: Discussionmentioning
confidence: 99%